Psycholinguistic insights into interaction patterns for meaning acquisition in BIPA learning at the university level - Nurhamidah, Didah; Rafli, Zainal; Murtadho, Fathiaty; Mahfuzo, Muhammad Rizal (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study investigates psycholinguistic perspectives on interaction patterns that facilitate meaning acquisition in BIPA (Bahasa Indonesia bagi Penutur Asing/Indonesian for Speakers of Other Languages) learning at UIN Syarif Hidayatullah Jakarta. Employing a descriptive-analytic qualitative approach, the research examines how specific interaction patterns namely Student-Centered, Reciprocal, Collaborative, and Authentic Interactive support cognitive and linguistic processes in second language acquisition. Data were collected through classroom observations, interviews with two instructors and eight students from culturally diverse backgrounds, and thematic analysis of relevant teaching materials. The findings highlight the effectiveness of interactive and contextually enriched teaching strategies in improving students’ grasp of literal and contextual meanings, vocabulary mastery, and cultural competence. Drawing on Krashen’s Input Hypothesis and Vygotsky’s Zone of Proximal Development, this study emphasizes the importance of comprehensible input and scaffolding in fostering meaningful learning. The practical outcomes include recommendations for psycholinguistics-based teacher training programs and the design of interactive instructional materials tailored to the needs of culturally diverse learners. These findings contribute to advancing BIPA teaching practices and strengthening Indonesia’s cultural diplomacy initiatives.AbstrakPenelitian ini mengkaji wawasan psikolinguistik terhadap pola interaksi yang mendukung pemerolehan makna dalam pembelajaran BIPA (Bahasa Indonesia bagi Penutur Asing) di UIN Syarif Hidayatullah Jakarta. Dengan pendekatan kualitatif deskriptif-analitis, penelitian ini menganalisis bagaimana pola interaksi seperti Student-Centered, Reciprocal, Collaborative, dan Authentic Interactive memfasilitasi proses kognitif dan linguistik dalam pemerolehan bahasa kedua. Data diperoleh melalui observasi kelas, wawancara dengan dua pengajar dan delapan siswa dari berbagai latar belakang budaya, serta analisis dokumen yang dianalisis secara tematik. Hasil penelitian menunjukkan bahwa strategi pengajaran yang interaktif dan kaya konteks efektif dalam meningkatkan pemahaman siswa terhadap makna literal dan kontekstual, penguasaan kosakata, dan wawasan budaya. Dengan mengintegrasikan teori seperti Input Hypothesis dari Krashen dan Zone of Proximal Development dari Vygotsky, penelitian ini menegaskan pentingnya comprehensible input dan scaffolding dalam menciptakan pengalaman belajar yang bermakna. Implikasi praktis dari penelitian ini mencakup perancangan program pelatihan guru berbasis psikolinguistik dan pengembangan bahan ajar interaktif yang disesuaikan dengan kebutuhan siswa dari latar belakang budaya yang beragam, sehingga berkontribusi pada peningkatan metode pengajaran BIPA dan mendukung diplomasi budaya Indonesia. How to Cite: Nurhamidah, D., Rafli, Z., Murtadho, F., &  Mahfuzo, M.R, (2024). Psycholinguistic insights into interaction patterns for meaning acquisition in BIPA learning at the university level. TARBIYA: Journal of Education in Muslim Society, 11(2), 197-210. https://doi.org/10.15408/tjems.v11i2.43364.